2019
DOI: 10.1089/tmj.2018.0147
|View full text |Cite
|
Sign up to set email alerts
|

A Prenatal Remote Monitoring Program in Pregnancies Complicated with Gestational Hypertensive Disorders: What Are the Contributors to the Cost Savings?

Abstract: Background: In 2015, we performed a cost analysis of a prenatal remote monitoring (RM) program compared with conventional care (CC) for women diagnosed with gestational hypertensive disorders (GHD). Introduction: We investigated where the cost savings were distributed by dividing our patient population into three subgroups, according to the gestational age (GA) at the time of delivery: (1) <34 weeks; (2) 34-37 weeks; and (3) >37 weeks of GA. Materials and Methods: Healthcare costs were calculated from patient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…Several studies have found that self-monitoring of BP is an effective means to monitor BP in the immediate postpartum period in women with preeclampsia. 3,[19][20][21] Cairns et al 3 reported that BP self-monitoring after a pregnancy affected by preeclampsia is a feasible strategy to assist with BP management. Blood pressure self-monitoring may be more cost effective than conventional obstetric follow-up care.…”
Section: Home Blood Pressure Monitoring and Preeclampsiamentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have found that self-monitoring of BP is an effective means to monitor BP in the immediate postpartum period in women with preeclampsia. 3,[19][20][21] Cairns et al 3 reported that BP self-monitoring after a pregnancy affected by preeclampsia is a feasible strategy to assist with BP management. Blood pressure self-monitoring may be more cost effective than conventional obstetric follow-up care.…”
Section: Home Blood Pressure Monitoring and Preeclampsiamentioning
confidence: 99%
“…Blood pressure self-monitoring may be more cost effective than conventional obstetric follow-up care. 20 Hirshberg et al 19 found that, after discharge, women with preeclampsia were more likely to submit BPs using text-based monitoring than attend a traditional office visit for BP follow-up. Currently, best practices regarding how often to evaluate and monitor women after preeclampsia remain unclear.…”
Section: Home Blood Pressure Monitoring and Preeclampsiamentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence‐based practices indicate that pregnancies complicated by pre‐eclampsia can be monitored closely on an outpatient basis with frequent clinic visits before delivery or inpatient hospital monitoring until delivery . Such monitoring could be achieved remotely, safely, and effectively through the combination of using mobile health (mHealth) technologies and outpatient services for appropriate management . A remote monitoring using mHealth in pregnant women during the prenatal period has shown positive results in decreasing healthcare costs and improving outcomes in newborns .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Such monitoring could be achieved remotely, safely, and effectively through the combination of using mobile health (mHealth) technologies and outpatient services for appropriate management. [3][4][5][6][7][8] A remote monitoring using mHealth in pregnant women during the prenatal period has shown positive results in decreasing healthcare costs and improving outcomes in newborns. 6,9 It offers patients the ability to better manage chronic conditions, transfers real-time information with integrated devices, improves clinical decision-making, provides necessary emergency care, and delivers patient care directly at their homes, which makes healthcare more accessible.…”
Section: Introductionmentioning
confidence: 99%